(NmASLI^NYE KULXTURY (B/s - (NmINKEWI^(B, (Ni(B.(Na(B.s; (NbORKOWSKIJ(B, (Nw(B.(Ne(B.s; (NwSESO@ZNYJ NAU^NO(B-(NISSLEDOWATELXSKIJ IN(B-(NT MASLI^NYH KULXTURs; (NmIN(B-(NWO SELXSKOGO HOZQJSTWA sssrs ((NmOSKWA (B:s (NsELXHOZGIZ(B,s, 1952)
(NzAKL(B. : (NS(B. 542-543s
(NiSPOLXZ(B. (NLIT(B. : (NS(B. 544-576s
Keywords: (NmASLI^NYE KULXTURYs